Social Media Marketing sebagai Peningkatan Literasi Digital Wali Murid MI Muhammadiyah Buntu - Arofah, Rifka Utami; Dwi Winarni; Defi Nurul Hayati; Titan Erillia; Said Akmala (Forum Kerjasama Pendidikan Tinggi, 2024)
Understanding digital literacy with the theme of Social Media Marketing is very important for MI Muhammadiyah Buntu Cilacap’s student parents. The biggest obstacle faced by our partners is the lack of open-mindedness and involvement of student parents in educational community resource development activities for both parents and students themselves. Therefore, this service activity is expected to improve the skills of utilizing digital marketing technology for getting additional income, so that it can spark the awareness of student parents to be able to contribute more financially to the progress of themselves and their families. Specifically, this activity aims to provide an understanding of the use of social media such as Facebook, WhatsApp, and Instagram, which can be used for digital marketing, including socialization about financial recording, as well as the use of homecare products that have the potential for business. This activity is expected to provide understanding and increase digital literacy to increase income by utilizing the latest technology, so that it is expected to be practiced in businesses that have been or will be run in order to adapt to current technological developments.